A plesiosaur (Reptilia, Sauropterygia) from the Cenomanian (Late Cretaceous) of Algora (Guadalajara Province, Central Spain). (November 2018) - Bardet, N.; Segura, M.; Pérez-García, A.
Abstract: A new Plesiosauria specimen from the Cenomanian (early Late Cretaceous) of Algora (Castilla-La-Mancha, Spain) is described here. It represents the first one found in this area and one of the few from the Cretaceous of Spain, being the only one preserving several bones. This is also one of the few plesiosaur specimen found in the Cretaceous of Europe. The specimen consists of a caudal vertebra and an almost complete pelvic girdle, whose character combination permits to refer it to an indeterminate Elasmosauridae. This is the first evidence of plesiosaur in the coastal marine outcrops of Algora, which has already yielded terrestrial, freshwater and coastal reptile taxa. This plesiosaur specimen can therefore represents either a carcass of a pelagic animal thrown on the coast by waves and currents (thanatocoenosis), or remains of an animal living in the area (biocoenosis).